2000
DOI: 10.1021/jf991025o
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Degradation of Triazine Derivatives in Aqueous Medium:  A Radiation and Photochemical Study

Abstract: Pulse and steady state radiolysis techniques have been used to determine the bimolecular rate constants and to investigate the spectral nature of the intermediates and the degradation induced by hydroxyl radicals ((*)OH) with 1,3,5-triazine (T), 2,4, 6-trimethoxy-1,3,5-triazine (TMT), and 2,4-dioxohexahydro-1,3, 5-triazine (DHT) in aqueous medium. A competitive kinetic method with KSCN as the (*)OH scavenger was used to determine the rate constants for the reaction of (*)OH with T, TMT, and DHT. The bimolecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 26 publications
4
15
0
Order By: Relevance
“…However, this linearity was observed only up to a concentration of Fe(II) as 10 −4 mol dm −3 above which this follows a saturation point (data not shown). Similar experiments were carried out using another triazine, DHT, which is known to have high reactivity with hydroxyl radical [16]. Radiolysis in the absence of Fe(II) showed a complete degradation after about 7000 Gy (Fig.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…However, this linearity was observed only up to a concentration of Fe(II) as 10 −4 mol dm −3 above which this follows a saturation point (data not shown). Similar experiments were carried out using another triazine, DHT, which is known to have high reactivity with hydroxyl radical [16]. Radiolysis in the absence of Fe(II) showed a complete degradation after about 7000 Gy (Fig.…”
Section: Resultssupporting
confidence: 59%
“…The pattern of reaction of • OH with a number of triazine derivatives is reasonably well documented [11,15,16]. • OH undergoes either addition or hydrogen abstraction reaction with atrazine [15,16]. It was also shown that the major end product of oxidation of atrazine by • OH is cyanuric acid (OOOT) [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The k OH value can be directly measured using pulse radiolysis, but this method requires specialized equipment ( Joseph et al, 2000).…”
Section: Experimentally Determined K Oh Values For Nitroaromaticsmentioning
confidence: 99%
“…In situ generation of OH by various methods such as photo-fenton reaction, 11 photolysis of ozone, 12 photolysis of hydrogen peroxide, 13 photochemical reactions of titanium dioxide, 14 radiolysis of water, 15 and sonochemical method 16 are the generally used AOPs. A considerable attempt has been made with AOPs based on ozone 17 and hydroxyl radicals [18][19][20] to investigate the complete degradation of triazines in the past. A number of reports demonstrated the high reactivity of OH with triazines (diffusion controlled) and have shown a degradation pathway in aqueous state.…”
Section: Introductionmentioning
confidence: 99%